Developing the leader within you - Maxwell, John C. (Nashville, Tennessee : Thomas Nelson, 1993)
Make your leadership library complete with John C. Maxwell's foundational classic Developing the Leader within You, a bestseller of over one million copies. Timeless principles applied in your life - and the life of your organization - will bring about positive change through personal integrity and self-discipline.
The Definition of leadership : Influence -- The Key to leadership : Priorities -- The Most important ingredient of leadership : Creating positive change -- The Quickest way to gain leadership : Problem solving -- The Extra plus in leadership : Attitude -- Developing your most appreciable asset : People -- The Indispensable quality of leadership : Vision -- The Price tag of leadership : Self-Discipline -- The Most important lesson of leadership : Staff development
Keywords: LEADERSHIP